Karakteristik Rempah dan Tantangannya Dalam Pengembangan Bumbu Basah Instan: Sebuah Review Singkat - Rezeki, Kartika Sri; Candra, Krishna Purnawan; Saragih, Bernatal (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Seasonings are various plant products with a fragrant aroma, such as galangal, turmeric, ginger, cinnamon, nutmeg, and pepper, and are used to flavor dishes. A more practical lifestyle and an increasing culinary industry have led to the development of the culinary industry to open business opportunities for processing instant wet spices to shorten cooking time. Instant seasoning is a mixture of various spices and seasonings that are mashed and processed into one. Instant seasoning processing requires safe and healthy handling, including freedom from pathogenic microbial contamination. Even though the spices have various functional activities including antibacterial, the development of instant wet seasonings is still facing a handicap of its microbiology safety. A broad contamination of bacteria, yeast and mold are still detected in the instant wet seasoning.